„Factors that affect construction project efficient realization in Republic of Macedonia“ - Žileska-Pančovska V., Ristevska-Jovanovska S., Mijoski G., Hanak T. (MASE - ДГКМ, 2013)
Construction project realization in Republic of Macedonia is determined by numerous factors. To find out their influences on construction project realization, a survey was made. Survey’ results, are grouped and analyzed into three groups. The first group is consists of factors related to external construction project influences. The second group is related to the factors relevant to the structure location and its surroundings. The third group is connected with the participants in construction project realization. The analyse findings shows that there are unused possibilities for reducing the negative impacts of the construction project realization determining factors in Republic of Macedonia.
Keywords: Construction project, realization, impact factors.